ANALISIS KEBIJAKAN PENDEKATAN TRANSDISIPLINER DALAM PENYELENGGARAAN TRIDHARMA PERGURUAN TINGGI PADA IAIN KENDARI - Akib Akib; Moh. Yahya Obaid (ITB AAS Indonesia Surakarta, 2024)
Abstract This research aims to determine and analyze the philosophical study of the transdisciplinary scientific approach at IAIN Kendari, the form of implementation of the tridharma of transdisciplinary-based higher education at IAIN Kendari in education and teaching, research and community service. This research uses a qualitative approach with a case study type. Collecting research data through observation, interviews and documentation. The results of the research show 1) IAIN Kendari's transdisciplinary scientific philosophical studies have a very strong ontological, epistemological and axiological basis, becoming Smart Bee as a philosophical description of its science. In his study, Smart Bee means that lecturers are smart bees who try to make students into smart campus bees. However, on a large scale, the academic community still has different perceptions regarding transdisciplinary studies which is the vision of IAIN Kendari, 2). The IAIN Kendari academic community does not yet have a common perception and understanding of the transdisciplinary approach to the tridharma of education and teaching, especially in relation to the KKNI and MBKM-based transdisciplinary curriculum model. Especially the study materials and paradigms used in the study program curriculum, study material for courses in the study program, learning carried out by lecturers to apply transdisciplinarity in lecture classes including student assignments given by lecturers have fulfilled the transdisciplinary approach, 3). That in conducting research, the transdisciplinary approach as a study paradigm on research topics and studies, for both lecturers and students, is still very difficult to implement. This can be seen from searching documents for lecturers' research reports and scientific papers in published journals. It is recommended that there is a need for a guidebook on the Concept and Implementation of the Transdisciplinary Approach established at the Institute to serve as a guideline in implementing this approach for the entire IAIN Kendari academic community and the formation of a scientific consortium that can elaborate the transdisciplinary approach in various scientific studies, research and community service both as formal objects or material objects. Keywords: Policy Analysis, Transdisciplinary, Tridharma of Higher Education.